Method selection for fabrication of small boat application of natural fibre composites - Misri, Sairizal; Leman, Zulkiflle; Salit, Mohd Sapuan; Ishak, Mohamad Ridzwan (2009)
The fibre glass boat is a familiar material used in boat industry. A lot of research on fabrication process such as lay-up, vacuum infusion mould and resin transfer mould has been conducted. Hybrid material of sugar palm fibre and fibre glass was used in fabricating the boat. This research investigates the method selection for fabrication of small boat application of natural fibre composites. The composite specimens made of different layer of fibres; woven glass fibre, strand mat, natural and hand woven of woven sugar palm fibres were prepared. The small boat were fabricated using a compression moulding and lay up technique. The results of the experiment showed that the best method for fabricating the small boat was compression moulding technique. As a general conclusion compression moulding technique is suitable to be used in making a small boat application of natural fibre composites.